Optimizing CRISPR/Cas9 Editing of Repetitive Single Nucleotide Variants - Usher, Inga; Ligammari, Lorena; Ahrabi, Sara; Hepburn, Emily; Connolly, Calum; Bond, Gareth L.; Flanagan, Adrienne M.; Cottone, Lucia (Frontiers in Genome Editing, 2022)
CRISPR/Cas9, base editors and prime editors comprise the contemporary genome editing toolbox. Many studies have optimized the use of CRISPR/Cas9, as the original CRISPR genome editing system, in substituting single nucleotides by homology directed repair (HDR), although this remains challenging. Studies describing modifications that improve editing efficiency fall short of isolating clonal cell lines or have not been validated at challenging loci or cell models. We present data from 95 transfections using two cell models comparing the effect on editing efficiency of donor template modifications, concentration of components, HDR enhancing agents and cold shock. We found that in silico predictions of guide RNA efficiency correlated poorly with in vitro activity. Using NGS and ddPCR we detected editing efficiencies of 5 to 12% in the transfected populations which fell to 1% on clonal cell line isolation. Our data demonstrate the variability of CRISPR efficiency by cell model, target locus and other factors. Successful genome editing requires a comparison of systems and modifications to develop the optimal protocol for the cell model and locus. We describe the steps in this process in a flowchart for those embarking on genome editing using any system and incorporate validated HDR-boosting modifications for those using CRISPR/Cas9.